COUNSELING GUIDANCE TO COMPLETE CHILDREN'S MENTAL IN CASE OF BULLYING IN THE SCHOOL ENVIRONMENT - Mutaqin, Asyif Zainal; Habibaturohman, Ai; Alawiyah, Neng Ely; Ghifari, Muhammad Fikri (CV. TOTUS TUUS, 2023)
Guidance and counseling on the mentality of students who are victims of bullying in schools is very influential. The effect of guidance and counseling is indicated by the improvement in the mental condition of students who are victims of bullying at school after individual treatment. This study aims to overcome the mentality of students who are victims of bullying at Waringin Middle School. The results showed that the mental health of students through four indicators of mental health, namely improving with scores before treatment 29.7% and after treatment 90.625%.